1995
DOI: 10.1111/j.1472-765x.1995.tb01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the effect of substrate concentration on the conjugal transfer rate of the TOL plasmid in short-term batch mating experiments

Abstract: Batch mating experiments with Pseudomonas putida PAW 1 (TOL) as a donor and Pseudomonas aeruginosa PAO 1162 as a recipient strain were performed to quantify the effect of the substrate concentration in the mating medium on the observed plasmid transfer rate coefficient. The impact of the substrate concentration in the mating medium was highly correlated with the growth history of the donor strain. When the donor strain was harvested in exponential growth phase, no impact was observed; when the donor strain was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, essentially no studies on horizontal gene transfer in subsurface microbial communities have been reported. Several reports have suggested that horizontal gene transfer in the environment occurs at lower rates than those observed in laboratory broth mating environments (4,32,40), and hence the incidence of gene transfer in the subsurface, with limited carbon fluxes and specific growth rates, may be small (14,46,47). Further, it is not clear how the rate and extent of horizontal gene transfer may be affected by the degree of environmental stress, such as the presence of heavy metals.…”
mentioning
confidence: 84%
“…However, essentially no studies on horizontal gene transfer in subsurface microbial communities have been reported. Several reports have suggested that horizontal gene transfer in the environment occurs at lower rates than those observed in laboratory broth mating environments (4,32,40), and hence the incidence of gene transfer in the subsurface, with limited carbon fluxes and specific growth rates, may be small (14,46,47). Further, it is not clear how the rate and extent of horizontal gene transfer may be affected by the degree of environmental stress, such as the presence of heavy metals.…”
mentioning
confidence: 84%
“…4), which was not fully developed until 6 days after the onset of germination, i.e., on the same day that the first transconjugants were detectable. Some studies indicate that plasmid transfer happens most efficiently when the availability of bacterial substrate is relatively high (29), and for the TOL plasmid it has been demonstrated that the physiological state of the recipient cells influence their ability to participate in transfer (7). We suggest that high concentrations of plant exudates around the root and the hypocotyl causes a high density of donors and putative recipients and perhaps also enhanced plasmid transfer and that these factors together explain why the large majority of transconjugants was observed in these zones of the seedlings (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities of the deep subsurface are constrained by the scarcity of growth substrates (60), water availability, and spatial separation (77), which result in low metabolic rates (28) and the dominance of chemolithoautotrophic metabolism (10,77). Because population densities (52) and metabolic activities (72) stimulate LGT, this process may be limited in the deep subsurface. Nevertheless, anecdotal evidence indicates that LGT affects the genetic and metabolic diversities of subsurface microbial communities.…”
mentioning
confidence: 99%